The globalising effect of commercialisation and commodification in African theological education - Naidoo, Marilyn ca. 20./21. Jh. (HTS teologiese studies, 2017)
The reality of globalisation is that it has knitted the world into a single time and place and has introduced the dominant force of consumerism. In adopting this framework, it has frayed the moral fabric of theological education and has short changed students who are configured as consumers to please rather than characters to build. While the demographic centre of faith has shifted southward, its ways of thinking and engaging culture have not yet caught up with that shift. Global interconnectedness and the globalisation of knowledge together with homogenisation forces have shaped African theological education to the extent that it has absorbed the almost irreversible traits of the West. This paper highlights how transnational cultural forms have profoundly impacted the production of theological education and will attempt a response to the homogenising forces by the focus of African identity.